Photobioreactor Limnospira indica Growth Model: Application From the MELiSSA Plant Pilot Scale to ISS Flight Experiment - Poughon, Laurent; Creuly, Catherine; Godia, Francesc; Leys, Natalie; Dussap, Claude-Gilles (Frontiers in Astronomy and Space Sciences, 2021)
Bioregenerative life support systems (BLSS) are the foundation stone to self-sustainable manned space missions. The MELiSSA is a BLLS concept that has evolved through a mechanistic engineering approach designed to acquire both theoretical and technical knowledge on each subsystem independently and, therefore, produce the necessary knowledge and experience needed to co-integrate all the subsystems together with a high level of control. One of the subsystems is a photobioreactor colonized by an axenic culture of the cyanobacterium Limnospira indica PCC8005 for revitalizing the air for the crew. This subsystem was extensively studied, and a mass balanced mechanistic model was developed to describe, predict and control the photobioreactor. The model was based on a light transfer limitation model coupled to a kinetic model for the cyanobacteria growth through a Linear Thermodynamics of Irreversible Processes (LTIP) approach, including substrate limitation. The model was integrated into several hydrodynamic models adapted to several photobioreactors design and experiments, from a 100 L airlift pilot scale ground photobioreactor to a 50 mL membrane photobioreactor for ISS flight. Through this paper we detail the principles of this mechanistic model and their application to different photobioreactor scales for predictive and descriptive simulations.